Effectiveness of and overdiagnosis from mammography screening in the Netherlands: population based study. (5th December 2017) - Autier, Philippe; Boniol, Magali; Koechlin, Alice; Pizot, Cécile; Boniol, Mathieu
Abstract: Objective: To analyse stage specific incidence of breast cancer in the Netherlands where women have been invited to biennial mammography screening since 1989 (ages 50-69) and 1997 (ages 70-75), and to assess changes in breast cancer mortality and quantified overdiagnosis. Design: Population based study. Setting: Mammography screening programme, the Netherlands. Participants: Dutch women of all ages, 1989 to 2012. Main outcome measures: Stage specific age adjusted incidence of breast cancer from 1989 to 2012. The extra numbers of in situ and stage 1 breast tumours associated with screening were estimated by comparing rates in women aged 50-74 with those in age groups not invited to screening. Overdiagnosis was estimated after subtraction of the lead time cancers. Breast cancer mortality reductions during 2010-12 and overdiagnosis during 2009-11 were computed without (scenario 1) and with (scenario 2) a cohort effect on mortality secular trends. Results: The incidence of stage 2-4 breast cancers in women aged 50 or more was 168 per 100 000 in 1989 and 166 per 100 000 in 2012. Screening would be associated with a 5% mortality reduction in scenario 1 and with no influence on mortality in scenario 2. In both scenarios, improved treatments would be associated with 28% reductions in mortality. Overdiagnosis has steadily increased over time with the extension of screening to women aged 70-75 and with the introduction of digital mammography. After deduction of clinical lead time cancers, 32% of cancers found in women invited to screening in 2010-12 and 52% of screen detected cancers would be overdiagnosed. Conclusions: The Dutch mammography screening programme seems to have little impact on the burden of advanced breast cancers, which suggests a marginal effect on breast cancer mortality. About half of screen detected breast cancers would represent overdiagnosis.